METODE DISKUSI PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Taufiq Ziaul Haq (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2019)
The use of discussion methods in Islamic religious education in SMP N 1 Demak. The purpose of this study is the effectiveness of the method in the learning of Islamic religion and its effect on learning in Kes XI SMP N 1 Demak. From data analysis to field research methods and data collection using interviews and observations, as well as literature studies. The results show that the method of discussion conducted at school in Islamic subjects has been effective and also affects students, students like learning that is fun and involved in learning. The effects of learning using group discussion methods are as diverse as increasing achievement, increasing social interaction, increasing activity, and increasing emotional intelligence.Keywords: Discussion Methods, Student Activeness, Benefits of Discussion